(untitled) (Academic Journal of Internal Affairs, 2024)
Aim: The article aims to explain the various concepts, tasks and interfaces of criminalistics, and to explore their relationship with police and forensic science, which often vary from author to author. Methodology: The study provides a synthesis by analysing domestic and foreign literature. Findings: Criminalistics is a possible and forward-looking formulation of the general methodology of fact-finding for law enforcement purposes, a scientific cognition within a legal framework, for legal purposes. It has a co-extensive relationship with law enforcement, with numerous interfaces and mutual interactions throughout their history. Forensic science is framed by criminalistics, but they are not identical. Value: The paper presents the complex relationship between forensic science and criminalistics, attempts to define forensic science, and discusses the Sydney Declaration and its significance.